The paraventricular nucleus and heart failure. Issue 2 (6th January 2014) - Pyner, Susan
<x xml:space="preserve">Abstract</x> New Findings What is the topic of this review? This review gives an update on the cellular and molecular mechanisms within the autonomic nervous system involved in non‐pathological and pathological cardiovascular regulation. What advances does it highlight? For cardiovascular homeostasis in non‐pathological conditions to be maintained, discrete neural networks using specified signalling mechanisms at both cellular and molecular levels are required. In heart failure, the cell signalling protein partners CAPON and PIN decrease the bioavailability of nitric oxide by inhibiting neuronal nitric oxide synthase activity, leading to the removal of tonic neuronal inhibition. Following a myocardial infarction, pro‐inflammatory cytokines in the paraventricular nucleus and the subsequent generation of reactive oxygen species, via angiotensin II activation of the angiotensin II type 1 receptor, increase neuronal excitability further, leading to sympathetic excitation. A pathological feature of heart failure is abnormal control of the sympathetic nervous system. The paraventricular nucleus of the hypothalamus (PVN) is one of the most important central sites involved in regulating sympathetic tone and is, in part, responsible for the dysregulation of the sympathetic nervous system evident in heart failure. Generation of sympathetic tone in response to fluctuations in cardiovascular regulation uses discrete anatomical pathways and neurochemical modulators. Direct and indirect projections from the PVN pre‐autonomic neurons innervate the sympathetic preganglionic neurons in the spinal cord, which in turn innervate sympathetic ganglia that give rise to the sympathetic nerves. Pre‐autonomic neurons of the PVN themselves receive an afferent input arising from the nucleus tractus solitarii, and viscerosensory receptors convey cardiovascular fluctuations to the nucleus tractus solitarii. The PVN contains excitatory and inhibitory neurons, whose balance determines the sympathetic tone. In non‐pathological conditions, the tonic inhibition of the PVN pre‐autonomic neurons is mediated by GABA‐ and NO‐releasing neurons. In heart failure, the pre‐autonomic neurons are disinhibited by the actions of the excitatory neurotransmitters glutamate and angiotensin II, leading to increased sympathetic activity. A key feature of the disinhibition is a reduction in the bioavailability of NO as a consequence of disrupted CAPON and PIN signalling mechanisms within the neuron. Another critical feature that contributes to increased neuronal excitation within the PVN is the production of pro‐inflammatory cytokines immediately following a myocardial infarction, the activation of the angiotensin II type 1 receptor and the production of reactive oxygen species. By examining the changes associated with the sympathetic nervous system pathway, we will progress our understanding of sympathetic regulation in heart failure, identify gaps in our knowledge and suggest new therapeutic strategies.